Two new species of the genus Typhlodromus Scheuten (Acari: Phytoseiidae) from Greece - Papadoulis, G.TH; Emmanouel, N.G. (ENTOMOLOGIA HELLENICA, 1990)
Adult females and males of two new Phytoseiid species, Typhlodromus pentelicus and Typhlodromus phylaktioticus, are described and illustrated. The former species was found on the bark of various trees while the latter was collected from Clematis sp. and Eragaria sp. in Greece.